Meeting report: GARNet/OpenPlant CRISPR-Cas workshop. Issue 1 (December 2016) - Parry, Geraint; Patron, Nicola; Bastow, Ruth; Matthewman, Colette
Abstract Targeted genome engineering has been described as a "game-changing technology" for fields as diverse as human genetics and plant biotechnology. One technique used for precise gene editing utilises the CRISPR-Cas system and is an effective method for genetic engineering in a wide variety of plants. However, many researchers remain unaware of both the technical challenges that emerge when using this technique or of its potential benefits. Therefore in September 2015, GARNet and OpenPlant organized a two-day workshop at the John Innes Centre that provided both background information and hands-on training for this important technology.